A general physics-based hardening law for single phase metals. (1st June 2022) - Zhang, Zhenjun; Qu, Zhan; Xu, Ling; Liu, Rui; Zhang, Peng; Zhang, Zhefeng; Langdon, Terence G.
Abstract: A simple exponential strain hardening model (ESH) has been developed in the framework of the Kocks-Mecking-Estrin formalism with a new microstructure-based parameter that accounts for the effect of yield strength. The relevant parameters reflecting the effect of the composition (or dislocation annihilation distance) and the microstructure type (or strengthening technology) are comprehensively analyzed. The application scope of the model is then briefly discussed, and several significant advantages are enumerated including the clear derivation processes and the explicit physical meaning of the various parameters. Finally, the ESH model is verified extensively by systematic tensile tests on six groups of Cu-Al alloys having more than one hundred microstructural states. In addition, significant and quantitative revelations of strength and uniform elongation for ductile metals are elaborated in the following manuscript. The present ESH model is of significant theoretical value in providing a detailed understanding of the tensile performance of metallic materials. Graphical Abstract: Image, graphical abstract